Effects of hydrogen peroxide addition on combustion characteristics of n-decane/air mixtures. (1st July 2018) - Gribi, Bouabdallah; Lin, Yuzhen; Hui, Xin; Zhang, Chi; Sung, Chih-Jen
Abstract: To curb the carbon footprint from the combustion of fossil fuels, hydrogen-enriched fuels have received much research attention in recent years. Hydrogen peroxide (H2 O2 ) has unique combustion characteristics, as it can be used as a fuel or serve as an oxidizer when reacting with other fuels. Considering the dual nature of H2 O2 and exploring its potential benefits in clean combustion technology, a numerical study is carried out to systematically investigate the effects of H2 O2 addition on combustion properties of n -decane/air mixtures, including ignition delay times, laminar flame speeds, extinction residence times, and emissions of CO and NOx . The results show that H2 O2 addition can greatly enhance the premixed combustion with shortened ignition delay times, increased laminar flame speeds, and extended extinction limits. While CO emissions increase with increasing H2 O2 addition for stoichiometric and lean n -decane/air mixtures, NOx emissions first increase with increasing H2 O2 addition and then decrease as air is completely replaced by H2 O2 . Sensitivity and reaction pathway analyzes are further conducted to identify the changes in controlling chemistry as a result of H2 O2 addition. It is found that the production of OH radicals are greatly enhanced by H2 O2 decomposition, and OH radicals play a dominant role in fuel oxidation process. The current simulation results suggest that reduced NOx emissions can be achieved with H2 O2 addition at leaner combustion conditions without compromising the static combustion stability.